2013
DOI: 10.1002/bmc.3100
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of imperatorin and its metabolites in vitro and in vivo by a GC‐MS method: application to a bioavailability and protein binding ability study in rat plasma

Abstract: In this study, a simple and sensitive gas chromatography-mass spectrometry method was developed for the study of bioavailability and protein binding and the metabolism of imperatorin in rat. The results showed that the pharmacokinetics of imperatorin after intravenous and oral administration in rats exhibited linear characteristics. The absolute bioavailability of imperatorin was calculated as ~3.85, ~33.51 and ~34.76% for 6.25, 12.5 and 25 mg/kg, respectively. The low bioavailability of imperatorin may be att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…31 Considering the variety of pharmacological properties displayed by IMP, it is clear that the compound has the potential for development as a pharmaceutical formulation for subsequent clinical assessment. 32 Because of the low bioavailability of IMP, which may be attributed to its poor absorption or extensive metabolism, 33 topical application of IMP would be of great interest for its future use in clinical treatments. However, the high nonpolarity of IMP becomes an obstruction for delivering through the stratum corneum and viable epidermis, which greatly limits the percutaneous penetration of IMP.…”
Section: Introductionmentioning
confidence: 99%
“…31 Considering the variety of pharmacological properties displayed by IMP, it is clear that the compound has the potential for development as a pharmaceutical formulation for subsequent clinical assessment. 32 Because of the low bioavailability of IMP, which may be attributed to its poor absorption or extensive metabolism, 33 topical application of IMP would be of great interest for its future use in clinical treatments. However, the high nonpolarity of IMP becomes an obstruction for delivering through the stratum corneum and viable epidermis, which greatly limits the percutaneous penetration of IMP.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of unbound drug was determined by the following equation: fu = Cu/Ct. Where fu is the fraction of unbound drug in plasma and Cu and Ct are the unbound and total concentrations of the drug in plasma, respectively [14,16].…”
Section: Ppb Studymentioning
confidence: 99%
“…It has been demonstrated that the PPB rate may affect the metabolic rates in the liver, the excretory rate from the kidney and the steady-state volume of distribution [16]. To date, equilibrium dialysis, microdialysis and ultrafiltration have become commonly available methods for measuring PPB [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Xanthotoxin and bergapten result from complex furanocoumarin degradation during metabolisation, and imperatorin is demethylated to xanthotoxin [40]. As a result, xanthotoxin and bergapten content was increased with in-the-shade and 40°C drying.…”
Section: Characterization Of Furanocoumarin Compounds In Baizhi Rootmentioning
confidence: 99%